Envolvimento de microRNAs na interação Carica papaya L. e Papaya meleira vírus com potencial biotecnológico - Abreu, Paolla Mendes do Vale de (2015)
Carica papaya L. is one of the most cultivated and consumed fruits in tropical and subtropical regions worldwide. Brazil is among the largest producers and exporters of papaya fruit. The pre-harvest diseases of papaya plants are the main limitation for fruit production. Papaya sticky disease is caused by the Papaya meleira virus (PMeV). It is a commercially important pathology in papaya culture potentially causing the complete loss of fruit production. Despite of this, little is known about the papaya interaction and response mechanisms against PMeV and there is not a papaya variety resistant to the virus. It is known that papaya 20S proteasome subunit levels of increase during PMeV infection, suggesting that proteolysis is an important feature of the plant defense response mechanisms. To date, 10,598 plant microRNAs have been identified in the Plant miRNAs Database (name of the DB), but only two microRNAs, miR162 and miR403, are from papaya. In this study, plant microRNA sequences were used to search for putative microRNAs in the papaya genome. A total of 462 microRNAs, representing 72 microRNA families, were predicted to occur in papaya. Out of these, the expression of 11 microRNAs, whose targets are known to be involved in 20S and 26S proteasomal degradation and in other stress response pathways, was estimated using real-time PCR, comparing healthy and infected papaya leaf tissues. The expression of miRNAs involved in proteasomal degradation increased in response to very low levels of PMeV titre and decreased as the viral titre increased. In contrast, biotic stress-related miRNAs levels decreased in papaya tissues infected with low virus titre and increased at high PMeV levels. Corroborating this results, analysed target genes for this miRNAs had their expression modulated in a dependent manner. With the results, some miRNAs were identified as relevant to the biotechnological application. This study represents a comprehensive prediction of miRNAs in papaya. The data presented here might help to complement the available molecular and genomic tools for the study of papaya. The differential expression of specific miRNAs and the modulation of their target genes will be helpful for understanding the particular interaction of PMeV and papaya responsible of disease development.